Radiological insights into fibromuscular dysplasia unveiled by intracranial aneurysms and iliac vein hypoplasia in suspected DVT - Abderrahmane Ibenyahia, MD; Oumaima Elkaddouri, MD; Mounir Salek, MD; Salma Boustani, MD; Soufiane Bigi, MD; Said Adnor, MD; Wassila Bouissar, MD; Soukaina Wakrim, MD (Radiology Case Reports)
Fibromuscular Dysplasia (FMD) is a nonatherosclerotic, noninflammatory vascular disorder predominantly affecting women aged 18 to 65 years. This case report highlights a 74-year-old female diagnosed with FMD incidentally during evaluation for deep vein thrombosis (DVT). Imaging revealed significant vascular anomalies, including a giant intracranial carotid aneurysm and a hypoplastic iliac vein with extensive collateral formation. Early detection and tailored management are crucial to prevent complications such as arterial dissections, aneurysms, and stroke. The patient showed favorable evolution without anticoagulation therapy, and interventional embolization was planned to mitigate rupture risks. Differential diagnosis includes atherosclerotic aneurysms, Ehlers-Danlos syndrome, Marfan syndrome, neurofibromatosis type 1, and polyarteritis nodosa, which must be distinguished through comprehensive imaging and clinical evaluation. The prognosis of FMD varies widely and depends on the extent and location of arterial involvement. This case underscores the importance of advanced imaging in accurately diagnosing and guiding long-term follow-up for FMD management.